Detect and analyse the concurrent flaws of the BPEL process in a VPN-based approach. (8th April 2020) - Cui, Puwen; Yang, Ru; Ding, Zhijun
Business Process Execution Language (BPEL) is a standard specification in service composition area. However, it is still lack of effective verification mechanisms based on formal methods. This paper describes a new modelling method for BPEL process by using a novel Petri net named variable Petri net (VPN). Several analysis methods are proposed to verify the concurrent flaws and an automated transformation and analysis tool is developed. Furthermore, the case study conducts a comparison with previous studies and validates the efficiency of our work.